2019
DOI: 10.2807/1560-7917.es.2019.24.17.1900114
|View full text |Cite
|
Sign up to set email alerts
|

Measles outbreak in Gothenburg urban area, Sweden, 2017 to 2018: low viral load in breakthrough infections

Abstract: In an outbreak of measles in Gothenburg, Sweden, breakthrough infections (i.e. infections in individuals with a history of vaccination) were common. The objective of this study was to compare measles RNA levels between naïve (i.e. primary) and breakthrough infections. We also propose a fast provisional classification of breakthrough infections. Medical records were reviewed and real-time PCR-positive samples genotyped. Cases were classified as naïve, breakthrough or vaccine infections. We compared clinical sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
39
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 25 publications
6
39
2
Order By: Relevance
“…In this study, an outbreak of measles reported at the Kansai International Airport in 2016 was investigated using quantitative real‐time polymerase chain reaction (PCR) and virus isolation. Because approximately 50% of patients with measles in this outbreak had vaccination records and showed modified clinical signs, it was considered a typical outbreak even after elimination of measles 13–15 . This study aimed to determine the quantity of viral load based on quantitative real‐time PCR and isolate the virus from clinical specimens to compare the virological features between patients with an immunologically naive status versus those with SVF.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, an outbreak of measles reported at the Kansai International Airport in 2016 was investigated using quantitative real‐time polymerase chain reaction (PCR) and virus isolation. Because approximately 50% of patients with measles in this outbreak had vaccination records and showed modified clinical signs, it was considered a typical outbreak even after elimination of measles 13–15 . This study aimed to determine the quantity of viral load based on quantitative real‐time PCR and isolate the virus from clinical specimens to compare the virological features between patients with an immunologically naive status versus those with SVF.…”
Section: Introductionmentioning
confidence: 99%
“…We agree, as stated in our paper, that there are reports of onward transmission of measles from cases with breakthrough infections in household settings. However, we do not conclude that the risk of measles transmission is limited to unvaccinated cases, but rather that ” …there was a large difference in viral load in nasopharyngeal samples between patients with naïve and breakthrough infections of measles, and our results indicate that a high risk of onward transmission is confined to naïve infections ” [1]. Thus, with our definition of breakthrough infection (history of vaccination and detectable IgG (high avidity) at rash onset (or within 4 days)), the risk of onward transmission is low in most cases.…”
mentioning
confidence: 62%
“…45 Reductions in vaccine coverage for a variety of reasons have resulted in the resurgence of vaccine-preventable diseases – most notably measles – with important health consequences. 46 51 Given the breadth and complexity of factors at play, public health officials need to find innovative ways to address individual immunization knowledge, attitudes, and beliefs, which are intrinsically linked to their healthcare providers and surrounding environment. 52 54 The European Vaccine Action Plan 2015–2020 etches this sentiment as it identifies tailored, innovative strategies as critical in reaching population groups with suboptimal vaccination coverage.…”
Section: A Digital Immunization System Of the Futurementioning
confidence: 99%